1. $12a^4b^5$
2. $25x^3y^5z$
3. $x(x-3)$
4. $4(x-2)$
5. $(x+2)(x-4)$
6. $x(x-7)(x+1)$
7. $(x+5)(x-5)$
8. $(x+3)(x-3)^2$
9. $(x+1)(x+2)(x+3)$
10. $(x-5)(x-2)(x+3)$
11. $\begin{array}[t]{rrl} \text{LCD}&=&10a^3b^2 \\ \\ \dfrac{3a}{5b^2}\cdot \dfrac{2a^3}{2a^3} &\Rightarrow &\dfrac{6a^4}{10a^3b^2} \\ \\ \dfrac{2}{10a^3b}\cdot \dfrac{b}{b} &\Rightarrow & \dfrac{2b}{10a^3b^2} \end{array}$
12. $\begin{array}[t]{rrl} \text{LCD}&=&(x-4)(x+2) \\ \\ \dfrac{3x}{(x-4)}\cdot \dfrac{(x+2)}{(x+2)}&\Rightarrow &\dfrac{3x^2+6x}{(x-4)(x+2)} \\ \\ \dfrac{2}{(x+2)}\cdot \dfrac{(x-4)}{(x-4)}&\Rightarrow &\dfrac{2x-8}{(x-4)(x+2)} \end{array}$
13. $\begin{array}[t]{rrl} \text{LCD}&=&(x-3)(x+2) \\ \\ \dfrac{(x+2)}{(x-3)}\cdot \dfrac{(x+2)}{(x+2)}&\Rightarrow &\dfrac{x^2+4x+4}{(x-3)(x+2)} \\ \\ \dfrac{(x-3)}{(x+2)}\cdot \dfrac{(x-3)}{(x-3)}&\Rightarrow &\dfrac{x^2-6x+9}{(x-3)(x+2)} \end{array}$
14. $\begin{array}[t]{rrl} \text{LCD}&=&x(x-6) \\ \\ \dfrac{5}{x^2-6x}&\Rightarrow &\dfrac{5}{x(x-6)} \\ \\ \dfrac{2}{x}\cdot \dfrac{(x-6)}{(x-6)}&\Rightarrow &\dfrac{2x-12}{x(x-6)} \\ \\ \dfrac{-3}{(x-6)}\cdot \dfrac{x}{x}&\Rightarrow & \dfrac{-3x}{x(x-6)} \end{array}$
15. $\begin{array}[t]{rrl} \text{LCD}&=&(x-4)^2(x+4) \\ \\ \dfrac{x}{x^2-16}\cdot \dfrac{(x-4)}{(x-4)}&\Rightarrow &\dfrac{x^2-4x}{(x-4)^2(x+4)} \\ \\ \dfrac{3x}{(x^2-8x+16)}\cdot \dfrac{(x+4)}{(x+4)}&\Rightarrow &\dfrac{3x^2+12}{(x-4)^2(x+4)} \end{array}$
16. $\begin{array}[t]{rrl} \text{LCD}&=&(x-5)(x+2) \\ \\ \dfrac{5x+1}{x^2-3x-10}&\Rightarrow &\dfrac{5x+1}{(x-5)(x+2)} \\ \\ \dfrac{4}{(x-5)}\cdot \dfrac{(x+2)}{(x+2)}&\Rightarrow &\dfrac{4x+8}{(x-5)(x+2)} \end{array}$
17. $\begin{array}[t]{rrl} \text{LCD}&=&(x+6)^2(x-6) \\ \\ \dfrac{x+1}{x^2-36}\cdot \dfrac{(x+6)}{(x+6)}&\Rightarrow &\dfrac{x^2+7x+6}{(x+6)^2(x-6)} \\ \\ \dfrac{(2x+3)}{(x^2+12x+36)}\cdot \dfrac{(x-6)}{(x-6)}&\Rightarrow &\dfrac{2x^2-9x-18}{(x+6)^2(x-6)} \end{array}$
18. $\begin{array}[t]{rrl} \text{LCD}&=&(x-4)(x+3)(x+1) \\ \\ \dfrac{(3x+1)}{(x^2-x-12)}\cdot \dfrac{(x+1)}{(x+1)}&\Rightarrow & \dfrac{3x^2+4x+1}{(x-4)(x+3)(x+1)} \\ \\ \dfrac{2x}{(x^2+4x+3)}\cdot \dfrac{(x-4)}{(x-4)}&\Rightarrow & \dfrac{2x^2-8x}{(x-4)(x+3)(x+1)} \end{array}$
19. $\begin{array}[t]{rrl} \text{LCD}&=&(x-3)(x+2) \\ \\ \dfrac{4x}{x^2-x-6}&\Rightarrow &\dfrac{4x}{(x-3)(x+2)} \\ \\ \dfrac{(x+2)}{(x-3)}\cdot \dfrac{(x+2)}{(x+2)}&\Rightarrow &\dfrac{x^2+4x+4}{(x-3)(x+2)} \end{array}$
20. $\begin{array}[t]{rrl} \text{LCD}&=&(x-4)(x-2)(x+5) \\ \\ \dfrac{3x}{x^2-6x+8}\cdot \dfrac{(x+5)}{(x+5)}&\Rightarrow & \dfrac{3x^2+15x}{(x-4)(x-2)(x+5)} \\ \\ \dfrac{(x-2)}{(x^2+x-20)}\cdot \dfrac{(x-2)}{(x-2)}&\Rightarrow & \dfrac{x^2-4x+4}{(x-4)(x-2)(x+5)} \\ \\ \dfrac{5}{(x^2+3x-10)}\cdot \dfrac{(x-4)}{(x-4)}&\Rightarrow & \dfrac{5x-20}{(x-4)(x-2)(x+5)} \end{array}$